Topics in Number Theory: In Honor of B. Gordon and S. Chowla - Ahlgren, Scott (Mathematics and Its Applications, 1999)
This volume contains the proceedings of the Topics in Number Theory Conference held at the Pennsylvania State University from July 31 through August 3, 1997. It contains seventeen research papers covering many areas of number theory; among them are contributions from four of the eight plenary speakers